Prevalence of Depression and its Associated Factors among Male Prisoners at Dillibazar Prison, Kathmandu, Nepal - Baral, Kushalata; Dahal, Maginsh; Khadka, Ganga; Adhikari, Anup (Europasian Journal of Medical Sciences, 2020)
Background: Depression is characterized by persistent low mood, lack of interest and low in energy. We conducted the study to find out the prevalence of depression and its associated factors among male prisoners in Dillibazar prison. Methods: A cross-sectional analytical design was conducted in 2018 among 195 male prisoners of Dillibazar by using systematic random sampling. The self-administered questionnaire technique was used for data collection along with the standard Major Depression Inventory (MDI) tool of WHO for rating the level of depression. The data were coded and tabulated using Epi-data. The analysis was done by SPSS 16 version. A chi-square test was done for the associations between the variables. Results: The study revealed that the prevalence of depression among male prisoners at Dillibazar prison was (45.6%).Among them, (28.2%) met the criteria of severe depression, (6.7%) moderate depression, while rest (10.8%), of mild depression. It was found that the duration of stay in prison, history of alcoholism, history of smoking, frequency of disputes is not statistically significant with depression. Depression was found a statistically significant association with p-values less than 0.05 at a 5% level of significance with a history of past illness and a history of drug abuse. Conclusion: Thus, we can conclude that half of the prisoners are having any kind of depression during their stay in prisoners. Thus this study will be useful in drawing the attention of the authorities towards the value of mental health among prisoners in Nepal. DOI: https://doi.org/10.46405/ejms.v2i1.21